Association of ABO blood type with mortality in hospitalized patients with COVID-19 - Vázquez-Medina , Martín Uriel; Cerda-Reyes , Eira; Barrón-Campos , Arcelia Carolina; Almeyda-Farfán, José Antonio; Ocharan-Hern´andez, Maria Esther; Vargas de León, Cruz (Horizonte Sanitario, 2021)
Introduction. The novel SARS-CoV-2 infection (COVID-19) has generated a global crisis. It is necessary to find prognosis factors for hospitalized patients with SARS-CoV-2, that help us to understand the observed difference in disease severity in patients with similar characteristics. The aim of this study was to explore the relation between ABO groups and in-hospital mortality in Mexican patients admitted with COVID-19. Study design and Methods. We performed a retrospective study with 2369 hospitalized patients with SARS-CoV-2 confirmed infection in a tertiary referral hospital, admitted from March 27 and December 10, 2020. Results. Type A blood was associated with a lower hazard of death among COVID-19 patients compared to type O (adjusted HR=0.72, 95% IC 0.55-0.95, P-value=0.02). Conclusions We found evidence of a significant association between ABO blood type and COVID-19 in-patients’ death. The blood group A may be less likely to death during hospitalization compared with group O.